Light-Assisted Enhancement of Gas Sensing Property for Micro-Nanostructure Electronic Device: A Mini Review - Ma, Zongtao; Wang, Ziying; Gao, Lingxiao (Frontiers in Chemistry, 2021)
In recent years, gas sensing electronic devices have always attracted wide attention in the field of environment, industry, aviation and others. In order to improve the gas sensing properties, many micro- and nano-fabrication technologies have been proposed and investigated to develop high-performance gas sensing devices. It is worth noting that light irradiation is an effective strategy to enhance gas sensitivity, shorten the response and recovery time, reduce operating temperature. In this review, firstly, the latest research advances of gas sensors based on different micro-nanostructure materials under UV light and visible light activation is introduced. Then, the gas sensing mechanism of light-assisted gas sensor is discussed in detail. Finally, this review describes the present application of gas sensors with improved properties under light activation assisted conditions and the perspective of their applications.